The Influence of Current Ratio and Debt To Asset Ratio on Financial Performance at PT Unilever Indonesia Tbk (Case Study on the Indonesian Stock Exchange for the 2015-2022 Period) - Sheli Selwina; Raden Rijanto (Formosa Journal of Social Sciences (FJSS), 2024)
This research was carried out to determine the influence of Current Ratio and Debt Asset Ratio on Financial Performance. The object of the research was carried out at PT Unilever Indonesia Tbk, with types of secondary data taken from the financial reports for 8 years from 2015-2022 which were divided into 3 parts. month. The type of research used is quantitative research with associative descriptive methods, with data collection techniques, namely using documentation techniques. The population in this research is the financial report for the year 2015-2022. The sampling technique in this research uses non-probability sampling. Meanwhile, the data analysis used is the classical assumption test which includes data normalization test, multicollinearity test, heteroscedasticity test and autocorrelation test, correlation test, coefficient of determination test and multiple linear regression, partial and simultaneous hypothesis testing. Based on the results of this research, it shows that the Current Ratio is partial. has a negative and significant effect on Financial Performance. Next, the Debt to Asset Ratio variable has no partial effect on the Financial Performance variable. Current Ratio and Debt to Asset Ratio have a simultaneous influence on the Financial Performance of PT Unilever Indonesia Tbk for the 2015-2022 period